Effects of Ischemic Postconditioning on the Hemodynamic Parameters and Heart Nitric Oxide Levels of Hypothyroid Rats - Jeddi,Sajad (2015)
Background: Ischemic postconditioning (IPost) is a method of protecting the heart against ischemia-reperfusion (IR) injury. However, the effectiveness of IPost in cases of ischemic heart disease accompanied by co-morbidities such as hypothyroidism remains unclear. Objective: The aim of this study was to determine the effect of IPost on myocardial IR injury in hypothyroid male rats. Methods: Propylthiouracil in drinking water (500 mg/L) was administered to male rats for 21 days to induce hypothyroidism. The hearts from control and hypothyroid rats were perfused in a Langendorff apparatus and exposed to 30 min of global ischemia, followed by 120 min of reperfusion. IPost was induced immediately following ischemia. Results: Hypothyroidism and IPost significantly improved the left ventricular developed pressure (LVDP) and peak rates of positive and negative changes in left ventricular pressure (±dp/dt) during reperfusion in control rats (p < 0.05). However, IPost had no add-on effect on the recovery of LVDP and ±dp/dt in hypothyroid rats. Furthermore, hypothyroidism significantly decreased the basal NO metabolite (NOx) levels of the serum (72.5 ± 4.2 vs. 102.8 ± 3.7 μmol/L; p < 0.05) and heart (7.9 ± 1.6 vs. 18.8 ± 3.2 μmol/L; p < 0.05). Heart NOx concentration in the hypothyroid groups did not change after IR and IPost, whereas these were significantly (p < 0.05) higher and lower after IR and IPost, respectively, in the control groups. Conclusion: Hypothyroidism protects the heart from IR injury, which may be due to a decrease in basal nitric oxide (NO) levels in the serum and heart and a decrease in NO after IR. IPost did not decrease the NO level and did not provide further cardioprotection in the hypothyroid group.